Unfolded‐protein response‐associated stabilization of p27(Cdkn1b) interferes with lens fiber cell denucleation, leading to cataract. Issue 3 (20th November 2015) - Lyu, Lei; Whitcomb, Elizabeth A.; Jiang, Shuhong; Chang, Min‐Lee; Gu, Yumei; Duncan, Melinda K.; Cvekl, Ales; Wang, Wei‐Lin; Limi, Saima; Reneker, Lixing W.; Shang, Fu; Du, Linfang; et al.
Abstract : Failure of lens fiber cell denucleation (LFCD) is associated with congenital cataracts, but the pathobiology awaits elucidation. Recent work has suggested that mechanisms that direct the unidirectional process of LFCD are analogous to the cyclic processes associated with mitosis. We found that lens‐specific mutations that elicit an unfolded‐protein response (UPR) in vivo accumulate p27(Cdkn1b), show cyclin‐dependent kinase (Cdk)‐1 inhibition, retain their LFC nuclei, and are cata‐ractous. Although a UPR was not detected in lenses expressing K6W‐Ub, they also accumulated p27 and showed failed LFCD. Induction of a UPR in human lens epithelial cells (HLECs) also induced accumulation of p27 associated with decreased levels of S‐phase kinase‐associated protein (Skp)‐2, a ubiquitin ligase that regulates mitosis. These cells also showed decreased lamin A/C phosphorylation and metaphase arrest The suppression of lamin A/C phosphorylation and metaphase transition induced by the UPR was rescued by knockdown of p27. Taken together, these data indicate that accumulation of p27, whether related to the UPR or not, prevents the phosphorylation of lamin A/C and LFCD in maturing LFCs in vivo, as well as in dividing HLECs. The former leads to cataract and the latter to metaphase arrest. These results suggest that accumulation of p27 is a common mechanism underlying retention of LFC nuclei.—Lei, L., Whitcomb, E. A., Jiang, S., Chang, M.‐L., Gu, Y., Duncan, M. K., Cvekl, A., Wang, W.‐L., Limi, S., Reneker, L. W., Shang, F., Du, L., Taylor, A., Unfolded protein response‐associated stabilization of p27(Cdkn1b) interferes with lens fiber cell denucleation, leading to cataract. FASEB J. 30, 1087–1095 (2016). www.fasebj.org